Solving systems of partial differential equations using object-oriented programming techniques with coupled heat and fluid flow as example. - Langtangen, Hans Petter (ACM transactions on mathematical software.)
This paper exploits object-oriented implementation techniques to facilitate the development computer codes for solving systems of coupled partial differential equations. We show how to build a simulator for equation systems by merging independent solvers for each equation that enters the system. The main goal is to obtain a rapid, robust, and reliable software development process with extensive reuse of implemented code. Coupled heat and fluid flow in pipes is used as example for illustrating the implementation techniques. We also present some results for the particular case of temperature-dependent generalized Newtonian fluid flow between two nonconcentric cylinders. The general applicability of the approach is discussed.